DEVELOPMENT OF GLOBAL DIVERSITY LKPD TEACHING MATERIALS FOR JAVANESE LANGUAGE IN ELEMENTARY SCHOOLS : PENGEMBANGAN BAHAN AJAR LKPD KEBHINEKAAN GLOBAL PADA MATA PELAJARAN BAHASA JAWA SD - Rika Fatmawati; Dwiana Asih Wiranti (Cerdas Proklamator, 2023)
Students' low understanding of the Javanese language, especially English manners, is among the challenges that students face in preserving their own culture. Indonesia has various tribes and cultures as well as mother tongues (dialects), the differences which combine to create its beauty. This research aims to develop Global Diversity LKPD teaching materials for Javanese language subjects to determine the effectiveness of teaching material products to improve students' understanding of the Javanese language krama inggil. The research methodology is developed using the ADDIE model in class V of SD Negeri 3 Jebol. The results of the needs analysis indicate that students experienced problems in understanding the Javanese language, krama inggil. Hence, the design of the LKPD teaching materials was global diversity by collecting vocabulary into four languages and using images of global diversity. The results of research on global diversity LKPD teaching materials show that the overall value of the material expert validation aspect was 78.3% and the media was 77.8% in the appropriate category. The results of the trial of the LKPD teaching materials with global diversity showed a difference in the average pretest of 34.64 and posttest of 54.48 for 25 students. Effectiveness is shown in learning outcomes through paired sample tests on SPSS 25, with a significant value (2-tailed) 0.000 < 0.05. There is a difference in the average learning outcomes before and after treatment using LKPD teaching materials with global diversity in Javanese language subjects in elementary school. It is customary to conclude that the development of LKPD teaching materials with global diversity makes learning effective in increasing students' understanding of the Javanese language, krama inggil.